Battery manufacturing method
The laminate structure with O2 type positive electrode and Li-containing negative electrode, combined with pre-discharge charging, addresses the internal pressure issue in batteries by managing volume expansion and enhancing cycle characteristics.
Patent Information
- Application Number
- JP2021136638
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-24
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-08-24
AI Technical Summary
Conventional battery technologies face challenges in effectively suppressing the increase in internal pressure during charging, particularly in all-solid-state batteries.
A manufacturing method involving a laminate structure with a positive electrode active material having an O2 type structure, a negative electrode active material containing Li, and an electrolyte layer, followed by discharging before the first charge to manage the internal pressure.
The method effectively suppresses the increase in internal pressure by allowing Li release from the negative electrode during discharge, reducing volume expansion and maintaining stable battery performance.
Smart Images

Figure 0007655148000001 
Figure 0007655148000002 
Figure 0007655148000003
Abstract
Description
[Technical field]
[0001] This application discloses a method for manufacturing a battery. [Background technology]
[0002] Patent Document 1 discloses a technique of using specific porous silicon particles as a negative electrode active material to suppress an increase in the battery's restraining pressure during charging. Patent Document 2 discloses a technique of using LiCoO2 having an O2 type structure as a positive electrode active material to suppress a decrease in the capacity retention rate of an all-solid-state battery. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-170605 A [Patent Document 2] JP 2019-169365 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the conventional technology, there is room for further improvement in terms of suppressing an increase in the restraining pressure (internal pressure) of a battery. [Means for solving the problem]
[0005] As one of the means for solving the above problems, the present application provides: obtaining a laminate including a positive electrode active material layer containing a positive electrode active material having an O2 type structure, a negative electrode active material layer containing a negative electrode active material containing Li, and an electrolyte layer provided between the positive electrode active material layer and the negative electrode active material layer; constraining the stack; and performing a first charge after discharging the restrained laminate; A method for manufacturing a battery comprising the steps of: Disclose.
[0006] In the manufacturing method of the present disclosure, before the discharging, the negative electrode active material layer may contain, as the negative electrode active material, simple Si and a Li—Si alloy.
[0007] The manufacturing method of the present disclosure may be a manufacturing method for an all-solid-state battery. Effect of the Invention
[0008] According to the manufacturing method of the present disclosure, an increase in the confining pressure (internal pressure) of the battery can be easily suppressed. [Brief description of the drawings]
[0009] [Figure 1] 1 shows the flow of a manufacturing method for a battery according to the present disclosure. [Diagram 2] 2 shows a schematic diagram of a laminate configuration. [Diagram 3] This shows the effect of the battery manufacturing method of the present disclosure. [Figure 4] 1 shows cycle characteristics of the batteries according to Example 1 and Comparative Example 1. [Diagram 5] 1 shows cycle characteristics of the batteries according to Example 2 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Fig. 1 shows a flow of a manufacturing method S10 of a battery according to an embodiment. Fig. 2 also shows a schematic configuration of a laminate 10 used in the manufacturing method S10. As shown in Figs. 1 and 2, the manufacturing method S10 of a battery includes obtaining a laminate 10 including a positive electrode active material layer 11 containing a positive electrode active material having an O2 type structure, a negative electrode active material layer 12 containing a negative electrode active material containing Li, and an electrolyte layer 13 provided between the positive electrode active material layer 11 and the negative electrode active material layer 12 (step S1), constraining the laminate 10 (step S2), and discharging the constrained laminate 10 and then charging it for the first time (step S3).
[0011] 1.Process S1 1 and 2, in step S1, a laminate 10 is obtained, which includes a positive electrode active material layer 11 containing a positive electrode active material having an O2 type structure, a negative electrode active material layer 12 containing a negative electrode active material containing Li, and an electrolyte layer 13 provided between the positive electrode active material layer 11 and the negative electrode active material layer 12. As shown in FIG. 2, the laminate 10 may further include a positive electrode current collector 14 and a negative electrode current collector 15.
[0012] 1.1 Cathode active material layer The positive electrode active material layer 11 includes at least a positive electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. The positive electrode active material layer 11 may also include various additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 11 may be appropriately determined according to the intended battery performance. The shape of the positive electrode active material layer 11 is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer 11 having a substantially flat surface. The thickness of the positive electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0013] 1.1.1 Cathode active material The positive electrode active material layer 11 contains a positive electrode active material having an O2 type structure. The O2 type structure may be composed of Li, at least one transition metal element, and O. The O2 type structure is a Li-deficient structure, and can take in Li by discharging as described later. The positive electrode active material having an O2 type structure may contain, for example, at least Li, at least one of Mn, Ni, and Co, and O as constituent elements. In particular, when the positive electrode active material contains at least Li, at least two of Mn, Ni, and Co, and O as constituent elements, the cycle characteristics of the battery are more likely to be improved.
[0014] The positive electrode active material with the O2 structure is Li x Mn a Ni b Co c O2±δ It may have the chemical composition shown. x, a, b, and c are not particularly limited as long as the O2-type structure can be maintained. For example, x satisfies 0 < x < 1. x may be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more, and may be 0.9 or less or 0.8 or less. Also, a, b, and c each satisfy 0 ≤ a < 1, 0 ≤ b < 1, and 0 ≤ c < 1. a may be 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, or 0.4 or more, and may be 0.9 or less, 0.8 or less, 0.7 or less, or 0.6 or less. b may be 0 or more or 0.1 or more, and may be 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. c may be 0 or more, 0.1 or more, or 0.2 or more, and may be 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, or 0.4 or less. a + b + c may be 0.8 or more or 0.9 or more, and may be 1.2 or less or 1.1 or less.
[0015] The positive electrode active material layer 11 may contain only the positive electrode active material having the above O2-type structure as the positive electrode active material. Alternatively, the positive electrode active material layer 11 may contain, in addition to the positive electrode active material having the above O2-type structure, a different type of positive electrode active material (other positive electrode active materials). From the viewpoint of further enhancing the effects of the technology of the present disclosure, the content of other positive electrode active materials in the positive electrode active material layer 11 may be small. For example, the positive electrode active material having the O2-type structure may occupy 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more of all the positive electrode active materials contained in the positive electrode active material layer 11.
[0016] A protective layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material. That is, the positive electrode active material layer 11 may include a composite having a positive electrode active material having an O2 type structure and a protective layer provided on the surface thereof. This makes it easier to suppress reactions between the positive electrode active material and sulfides (e.g., sulfide solid electrolytes described later, etc.). Examples of Li-ion conductive oxides include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, and Li2WO4. The coverage (area ratio) of the protective layer may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.
[0017] The shape of the positive electrode active material may be any shape that is common for battery active materials. For example, the positive electrode active material may be particulate. The positive electrode active material particles may be solid particles or hollow particles. The positive electrode active material particles may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the positive electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. The average particle diameter D50 in the present application is the particle diameter (median diameter) at an integrated value of 50% in a volume-based particle size distribution obtained by a laser diffraction / scattering method.
[0018] 1.1.2 Electrolytes The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolytic solution). When an all-solid-state battery is manufactured, the positive electrode active material layer 11 may contain a solid electrolyte as the electrolyte. When an electrolyte battery is manufactured, the positive electrode active material layer 11 may contain an electrolytic solution as the electrolyte.
[0019] The solid electrolyte may be any known solid electrolyte for batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, the inorganic solid electrolyte has a higher ionic conductivity than the organic polymer electrolyte. In addition, the inorganic solid electrolyte has a higher heat resistance than the organic polymer electrolyte. Examples of the inorganic solid electrolyte include lithium lanthanum zirconate, LiPON, and Li 1+X Al X Ge 2-X Examples of the solid electrolyte include oxide solid electrolytes such as (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass; and sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. In particular, the performance of the sulfide solid electrolyte, particularly the sulfide solid electrolyte containing Li2S-P2S5, is high. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, particulate. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.
[0020] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be an aqueous electrolyte or a non-aqueous electrolyte. The composition of the electrolyte may be the same as that of the electrolyte of a lithium ion battery. For example, the electrolyte may be a carbonate-based solvent in which a lithium salt is dissolved at a predetermined concentration. Examples of the carbonate-based solvent include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of the lithium salt include LiPF6.
[0021] 1.1.3 Conductive additives Examples of the conductive assistant include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0022] 1.1.4 Binders Examples of the binder include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.
[0023] 1.2 Negative electrode active material layer The negative electrode active material layer 12 contains at least a negative electrode active material, and may further contain an electrolyte, a conductive assistant, a binder, and the like. The negative electrode active material layer 12 may also contain various additives. The contents of the negative electrode active material, electrolyte, conductive assistant, binder, and the like in the negative electrode active material layer 12 may be appropriately determined according to the intended battery performance. The shape of the negative electrode active material layer 12 is not particularly limited, and may be, for example, a sheet-like negative electrode active material layer having a substantially flat surface. The thickness of the negative electrode active material layer 12 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0024] 1.2.1 Negative electrode active material The negative electrode active material layer 12 contains a negative electrode active material containing Li. In the negative electrode active material layer 12, a negative electrode active material not containing Li and a negative electrode active material containing Li may be mixed. As the negative electrode active material, various materials having a potential (charge / discharge potential) at which lithium ions are absorbed and released that is lower than the above-mentioned positive electrode active material may be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, and the like may be used. Only one type of negative electrode active material may be used alone, or two or more types may be used in combination.
[0025] According to the findings of the present inventors, when the negative electrode active material layer 12 contains a Si simple substance and a Li-Si alloy as the negative electrode active material, the discharge capacity of the battery is likely to be improved. Specifically, when the negative electrode active material layer 12 contains both a Si simple substance and a Li-Si alloy as the negative electrode active material, the amount of Li inserted into the positive electrode active material having the above-mentioned O2 type structure during discharge is greater than when the negative electrode active material layer 12 contains only a Si simple substance. That is, an amount of Li exceeding the amount of Li that the positive electrode active material had initially (before charging and discharging) can be inserted into the positive electrode active material. In addition, when the negative electrode active material layer 12 contains only a Si simple substance as the negative electrode active material, discharge cannot be performed before the first charge. On the other hand, when the negative electrode active material layer 12 contains only a Li-Si alloy as the negative electrode active material, there is a risk that the amount of Li that can be absorbed in the negative electrode active material layer 12 will decrease.
[0026] The composition of the Li-Si alloy is not particularly limited. For example, the Li-Si alloy may be α S β The Li-Si alloy may have a composition represented by (0<α / β≦4.4). α / β may be 0.1 or more, 0.5 or more, or 1.5 or more. Specific examples of Li-Si alloys include Li 0.54 Si, Li 0.87 Si, Li 1.2 Si, Li 2.2 Si, Li 3.75 Si, Li 4.4 Examples include Si.
[0027] The mass ratio of the Li-Si alloy to the total of the Si elemental substance and the Li-Si alloy contained in the negative electrode active material layer 12 is not particularly limited. For example, the mass ratio may be 10.0 mass% or more and 90.0 mass% or less. According to the findings of the present inventors, by adjusting the mass ratio of the Si elemental substance and the Li-Si alloy to the above range, the discharge capacity of the battery is more likely to be improved significantly even when a positive electrode active material having an O2 type structure is used. The mass ratio of the Li-Si alloy to the total of the Si elemental substance and the Li-Si alloy may be 20.0 mass% or more, 30.0 mass% or more, 40.0 mass% or more, or 50.0 mass% or more, and may be 85.0 mass% or less, 80.0 mass% or less, 75.0 mass% or less, or 70.0 mass% or less. In particular, when the mass ratio is 50.0 mass% or more and 75.0 mass% or less, the discharge capacity of the battery can be improved more significantly.
[0028] The shape of the negative electrode active material may be any shape that is common for negative electrode active materials in batteries. For example, the negative electrode active material may be in the form of particles. The negative electrode active material particles may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less.
[0029] 1.2.2 Electrolytes, Conductive Aids and Binders Examples of the electrolyte that can be contained in the negative electrode active material layer 12 include the above-mentioned solid electrolyte and electrolytic solution. When an all-solid-state battery is manufactured, the performance of the battery is likely to be improved when the negative electrode active material layer 12 contains a solid electrolyte, particularly a sulfide solid electrolyte, and further, a sulfide solid electrolyte containing Li2S-P2S5. Examples of the conductive assistant that can be contained in the negative electrode active material layer 12 include the above-mentioned carbon material and the above-mentioned metal material. The binder that can be contained in the negative electrode active material layer 12 may be appropriately selected from, for example, those exemplified as the binder that can be contained in the above-mentioned positive electrode active material layer 11.
[0030] 1.3 Electrolyte layer The electrolyte layer 13 contains at least an electrolyte. When an all-solid-state battery is manufactured, the electrolyte layer 13 contains a solid electrolyte and may further contain a binder or the like. In this case, the content of the solid electrolyte and the binder or the like in the electrolyte layer 13 is not particularly limited. On the other hand, when an electrolyte battery is manufactured, the electrolyte layer 13 contains an electrolyte solution and may further have a separator or the like for holding the electrolyte solution and preventing contact between the positive electrode active material layer 11 and the negative electrode active material layer 12. The thickness of the electrolyte layer 13 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0031] The solid electrolyte, the electrolytic solution, the binder, and the like are as described above. The separator may be any separator that is commonly used in lithium ion batteries, and may be made of resin such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.
[0032] 1.4 Positive electrode current collector As shown in FIG. 2, the laminate 10 may include a positive electrode collector 14 in contact with the positive electrode active material layer 11. The positive electrode collector 14 may be any of those commonly used as a positive electrode collector for a battery. The positive electrode collector 14 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The positive electrode collector 14 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 14 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 14 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode collector 14 may contain Al. The positive electrode collector 14 may have some kind of coating layer on its surface for the purpose of adjusting resistance, or the like. The positive electrode current collector 14 may be a metal foil or a substrate plated or vapor-deposited with the above metal. When the positive electrode current collector 14 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the positive electrode current collector 14 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, or 1 mm or less or 100 μm or less.
[0033] 1.5 Negative electrode current collector As shown in FIG. 2, the laminate 10 may include a negative electrode current collector 15 in contact with the negative electrode active material layer 12. The negative electrode current collector 15 may be any of those commonly used as a negative electrode current collector for a battery. The negative electrode current collector 15 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The negative electrode current collector 15 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 15 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 15 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 15 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 15 may have some kind of coating layer on its surface for the purpose of adjusting the resistance, etc. The negative electrode current collector 15 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. When the negative electrode current collector 15 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 15 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0034] 1.6 Method for obtaining the laminate The manufacturing method S10 is characterized in that discharge is performed before the first charge, as described later, and the manufacturing conditions of the laminate 10, which is the previous step, are not particularly limited and may be the same as those in the conventional battery manufacturing method. For example, the positive electrode active material layer 11, the negative electrode active material layer 12, and the electrolyte layer 13 can be easily formed by forming a mixture containing the above-mentioned various components in a dry or wet manner, and the laminate 10 can be easily obtained by stacking each layer. The laminate 10 only needs to have at least one each of the positive electrode active material layer 11, the negative electrode active material layer 12, and the electrolyte layer 13. In the laminate 10, the capacity of the positive electrode and the capacity of the negative electrode may be appropriately determined according to the performance of the target battery. For example, the ratio C1 / C2 of the capacity C1 of the positive electrode to the capacity C2 of the negative electrode may be 0.1 or more or 0.2 or more, and may be 1.0 or less or 0.9 or less.
[0035] 2.Process S2 In step S2, the laminate 10 obtained as described above is restrained. The laminate 10 may be restrained, for example, by housing the laminate 10 inside an exterior body (not shown), or by applying a restraining pressure to the laminate 10 by a restraining member (not shown). However, in the technology of the present disclosure, the presence of an exterior body or a restraining member is optional.
[0036] 2.1 Exterior The exterior body can be any known exterior body for a battery. For example, it may be made of a laminate film or may be something else. The laminate 10 can be housed inside the exterior body by a known method. For example, the laminate 10 may be enclosed in the laminate film by housing a portion of the laminate 10 excluding tabs, terminals, etc., in the laminate film and then sealing the laminate film. In this way, by housing the laminate 10 inside the exterior body, the laminate 10 can come into contact with the inner wall of the exterior body and be restrained.
[0037] 2.2 Restraining members The restraining member may be any of those known as battery restraining members. The restraining member may restrain the laminate 10 from the outside of the above-mentioned exterior body, or may restrain the laminate 10 inside the exterior body. The restraining member may, for example, apply a restraining pressure to the laminate 10 at least in the stacking direction. That is, the direction of the restraining pressure by the restraining member may be aligned with the stacking direction of the positive electrode active material layer 11, the electrolyte layer 13, and the negative electrode active material layer 12. This can reduce the interface resistance in each layer, and a battery with even more excellent cycle characteristics can be obtained. The restraining pressure by the restraining member is not particularly limited, and may be, for example, 1 MPa or more and 20 MPa or less.
[0038] 3.Process S3 In step S3, the restrained laminate 10 is discharged and then charged for the first time. Step S3 can be performed using a known charge / discharge device or the like. The discharge end potential and charge end potential in step S3 are not particularly limited and may be appropriately determined depending on the desired battery performance.
[0039] As shown in FIG. 3 as a conventional technique, if the first charge is performed on the laminate 10 without discharging, the restraining pressure (internal pressure) after charging increases significantly due to the volume expansion of the negative electrode. In contrast, in the manufacturing method S10, the first charge is performed after discharging the laminate 10. As described above, in the laminate 10, a positive electrode active material having an O2 type structure is adopted for the positive electrode active material layer 11, while a negative electrode active material containing Li is adopted for the negative electrode active material layer 12. That is, before the first charge, Li can be released from the negative electrode active material by discharging, and the Li released from the negative electrode active material can be absorbed into the positive electrode active material. At this time, the volume of the negative electrode shrinks, and the restraining pressure (internal pressure) decreases. In this way, in the manufacturing method S10, the first charge is performed after the restraining pressure (internal pressure) is reduced by discharging, so that the increase in the restraining pressure (internal pressure) after charging is suppressed as shown in FIG. 3.
[0040] In this application, "the increase in the confining pressure (internal pressure) is suppressed" means that the maximum value of the confining pressure (internal pressure) is lowered, as shown in Fig. 3. It is believed that such an effect is achieved regardless of the type of battery (all-solid-state battery, electrolyte battery) that is the product, but it is believed that the effect of suppressing the increase in the confining pressure is particularly remarkable in the case of an all-solid-state battery.
[0041] 4.Other processes In addition to the above steps S1 to S3, the manufacturing method S10 may include a general step for a battery manufacturing method. For example, a step of connecting terminals to the laminate 10. In the manufacturing method S10, a plurality of batteries may be electrically connected and stacked in any manner to form a battery pack. In this case, the battery pack may be housed inside a known battery case. The shape of the battery obtained by the manufacturing method S10 may be, for example, a coin type, a laminate type, a cylindrical type, a square type, or the like.
[0042] 5. Supplementary Information In addition, in addition to the positive electrode active material having the above-mentioned O2 type structure, there are also positive electrode active materials having an O3 type structure. However, such positive electrode active materials do not substantially have a Li-deficient structure, and cannot absorb Li by discharging immediately after the production of the laminate 10. That is, a battery can only be manufactured by starting charging as shown in the conventional technology of FIG. 3. In this case, the volume expansion of the negative electrode is large, and the restraining pressure (internal pressure) increases significantly. In contrast, as described above, in the manufacturing method S10, a battery can be manufactured by starting discharging as shown in FIG. 3 by combining a positive electrode active material having an O2 type structure with a negative electrode active material containing Li, and the increase in the restraining pressure (internal pressure) can be suppressed by the above-mentioned mechanism. EXAMPLES
[0043] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.
[0044] 1. Production and evaluation of all-solid-state batteries 1.1 Example 1 1.1.1 Positive electrode active material with O2 structure (Li 0.7 Mn 0.5 Ni 0.2 Co 0.3 Preparation of O2 Solution 1 was obtained by dissolving 43.06 g of Mn(NO3)2·6H2O, 17.97 g of Ni(NO3)2·6H2O, and 26.98 g of Co(NO3)2·6H2O in 250 g of pure water. Solution 2 was obtained by dissolving 31.8 g of Na2CO3 and 10.1 mL of ammonia water in 250 g of pure water. Solutions 1 and 2 were simultaneously dropped into a beaker containing 100 mL of pure water to obtain a mixed solution. The resulting mixed solution was stirred at 50 °C overnight. After stirring, the mixed solution was washed with pure water and then dried at 120 °C for more than 48 hours to obtain intermediate substance 1 ((Mn 0.5 Ni 0.2 Co 0.3 )CO3) was obtained.
[0045] 13.5 g of intermediate substance 1 and 4.28 g of Na2CO3 were mixed in a mortar and pressed with a hydrostatic press, then held at 600°C for 6 hours and then held at 900°C for 24 hours for firing to obtain intermediate substance 2 (Na 0.7 Mn 0.5 Ni 0.2 Co 0.3 O2) was obtained.
[0046] 3.5 g of intermediate substance 2, 4.77 g of LiCl, and 7.75 g of LiNO3 were mixed and dissolved by holding at 280 °C for 1 hour. After that, it was washed with pure water, filtered and dried to obtain Li as a positive electrode active material. 0.7 Mn 0.5 Ni 0.2 Co 0.3 Got O2.
[0047] 1.1.2 Coating of the positive electrode active material Li as a positive electrode active material 0.7 Mn 0.5 Ni 0.2 Co 0.30.2 g of O2, 0.11747 g each of Nb solution (containing Li ions and Nb source) and water were weighed out and mixed in an agate mortar to obtain a mixture of powder and solution. After the mixture was mixed uniformly, the agate mortar was heated on a hot plate set at 80°C while mixing the mixture, and the solution was evaporated to obtain a powder. The obtained powder was vacuum-dried at 200°C for 5 hours to obtain a composite having a positive electrode active material and a protective layer formed on its surface (Nb-coated Li 0.7 Mn 0.5 Ni 0.2 Co 0.3 O2) was obtained.
[0048] 1.1.3 Preparation of solid electrolyte A mixture was obtained by mixing 0.550g of Li2S (Furuuchi Chemical Co., Ltd.), 0.887g of P2S5 (Aldrich Co., Ltd.), 0.285g of LiI (Nippo Chemical Co., Ltd.), and 0.277g of LiBr (Kojundo Chemical Co., Ltd.) in an agate mortar. 4g of n-heptane was added to the mixture, and mechanical milling was performed for 40 hours using a planetary ball mill to obtain a solid electrolyte (Li2S-LiBr-LiI-P2S5).
[0049] 1.1.4 Preparation of positive electrode mixture 1.5 g of the above composite as a positive electrode active material, 0.023 g of VGCF as a conductive additive, 0.239 g of a solid electrolyte, and 0.8 g of butyl butyrate were mixed with an ultrasonic homogenizer (UH-50, manufactured by SMT Corporation) to obtain a positive electrode mixture.
[0050] 1.1.5 Preparation of negative electrode active material containing Li By mixing 0.44g of metallic Li and 0.375g of elemental Si in an agate mortar, a Li-Si alloy (Li 15 The Li-Si alloy thus obtained and elemental Si were mixed in a mass ratio of 62.5:37.5 to obtain a negative electrode active material.
[0051] 1.1.6 Preparation of negative electrode mixture 1.0 g of the above negative electrode active material, 0.04 g of VGCF as a conductive assistant, 0.776 g of the above solid electrolyte, and 1.7 g of n-heptane were mixed with an ultrasonic homogenizer (UH-50, manufactured by SMT Corporation) to obtain a negative electrode mixture.
[0052] 1.1.7 Preparation of solid electrolyte layer Ceramic mold (cross-sectional area: 1 cm 2 ) and add 0.065g of the above solid electrolyte to it, and 2 A solid electrolyte layer was formed by pressing the resultant mixture at 0.5° C. for 1 hour.
[0053] 1.1.8 Laminate Creation and Constraint 0.018 g of the above positive electrode mixture was laminated on one side of the solid electrolyte layer, and 1 ton / cm 2 On the other side of the solid electrolyte layer, 0.0054 g of the negative electrode mixture was laminated and pressed with a pressure of 4 ton / cm. 2 A negative electrode active material layer was formed by pressing the positive electrode current collector (aluminum foil) on the positive electrode active material layer side and the negative electrode current collector (copper foil) on the negative electrode active material layer side to obtain a laminate, and the laminate was contained and restrained in an exterior body.
[0054] 1.1.9 Discharging the stack and first charging The laminate obtained as described above was discharged to 1.8 V while maintaining the fixed dimensional constraint, and then charged for the first time to 4.6 V to obtain an all-solid-state battery for evaluation. After charging was completed, the constraint pressure of the battery was measured.
[0055] 1.1.10 Cycle test The solid-state battery for evaluation was repeatedly charged at a constant current and constant voltage of 0.1C (CC)-0.01C (CV) up to 4.6V, and then discharged at a constant current and constant voltage of 0.1C (CC)-0.01C (CV) up to 1.8V in a thermostatic chamber at 25°C, and the discharge capacity at each cycle was confirmed.
[0056] 1.2 Comparative Example 1 A laminate was obtained in the same manner as in Example 1, and the first charge was performed to 4.6 V without discharging while maintaining the fixed size constraint, to obtain an all-solid-state battery for evaluation. After the charge was completed, the constraint pressure of the battery was measured. In addition, a cycle test was performed under the same conditions as in Example 1 for the all-solid-state battery for evaluation, and the discharge capacity in each cycle was confirmed.
[0057] 1.3 Evaluation results When the confining pressure of the battery after the first charge was compared between Example 1 and Comparative Example 1, the confining pressure of Example 1 was 14% lower than that of Comparative Example 1. As shown in Fig. 3, in Comparative Example 1, the negative electrode expanded significantly due to the start of charge, resulting in a large increase in the confining pressure, whereas in Example 1, the volume of the negative electrode was contracted as the start of discharge, reducing the confining pressure, and then charging was performed, which is believed to be why the increase in the confining pressure (maximum confining pressure) was smaller.
[0058] Fig. 4 shows the cycle test results of the batteries according to Example 1 and Comparative Example 1. As shown in Fig. 4, Example 1 had cycle characteristics and capacity equal to or greater than those of Comparative Example 1. In Example 1, the confining pressure could be kept lower than that of Comparative Example 1, and as a result, cracks in the battery material could be suppressed, which is believed to have led to improved cycle characteristics.
[0059] 2. Manufacture and evaluation of electrolyte batteries 2.1 Example 2 2.1.1 Preparation of the positive electrode 85% by mass of the positive electrode active material, 10% by mass of acetylene black (LI400) as a conductive agent, and 5% by mass of polyvinylidene fluoride as a binder were mixed and slurried with N-methyl-2-pyrrolidone, and then coated on a positive electrode current collector made of aluminum foil. After that, the mixture was vacuum dried at 120°C and molded to obtain a positive electrode.
[0060] 2.1.2 Preparation of the negative electrode For the negative electrode, lithium metal cut to a specified size was used.
[0061] 2.1.3 Preparation of electrolyte The non-aqueous electrolyte used was a Daikin electrolyte (1.0M LiPF6 / TW5(TFPC)+F3(TFEMC) 30:70vol%+ TL16(LiDFOB 0.98wt%)).
[0062] 2.1.4 Coin cell fabrication The above-mentioned electrolyte solution was poured into a coin-type cell using the above-mentioned positive electrode and negative electrode in an inert atmosphere to prepare a coin cell.
[0063] 2.1.5 Discharging and First Charge of Coin Cell The coin cell obtained as described above was discharged to 2.0 V while maintaining the fixed size constraint, and then charged for the first time to 4.8 V to obtain an electrolyte battery for evaluation. After charging was completed, the constraint pressure of the battery was measured.
[0064] 2.1.6 Cycle test A cycle test was carried out under the same test conditions as in Example 1 and Comparative Example 1, and the discharge capacity in each cycle was confirmed.
[0065] 2.2 Comparative Example 2 A coin cell was obtained in the same manner as in Example 1, and while maintaining the fixed size constraint, the first charge was performed up to 4.8 V without discharging to obtain an electrolyte battery for evaluation. In addition, a cycle test was performed on the electrolyte battery for evaluation under the same conditions as in Example 2 to confirm the discharge capacity in each cycle.
[0066] 2.3 Evaluation results When the confining pressure of the battery after the first charge was compared between Example 2 and Comparative Example 2, the internal pressure of the battery in Example 2 was 12% lower than that in Comparative Example 2. As shown in Fig. 3, in Comparative Example 2, the negative electrode expanded significantly due to the start of charge, resulting in a large increase in the confining pressure, whereas in Example 2, the volume of the negative electrode was contracted as the start of discharge, reducing the confining pressure, and then charging was performed, which is believed to be why the increase in the confining pressure (maximum confining pressure) was smaller.
[0067] Fig. 5 shows the cycle test results of the batteries according to Example 2 and Comparative Example 2. As shown in Fig. 5, Example 2 had cycle characteristics and capacity equal to or greater than those of Comparative Example 2. In Example 2, the confining pressure could be kept lower than that of Comparative Example 2, and as a result, cracks in the battery material could be suppressed, which is believed to have led to improved cycle characteristics.
[0068] 3. Summary As described above, it can be said that the battery manufacturing method including the following steps (1) to (3) can suppress an increase in the restraining pressure (internal pressure) of the battery. (1) To obtain a laminate including: a positive electrode active material layer containing a positive electrode active material having an O2 type structure; a negative electrode active material layer containing a negative electrode active material containing Li; and an electrolyte layer provided between the positive electrode active material layer and the negative electrode active material layer. (2) Restraining the laminate. (3) The restrained laminate is discharged and then charged a first time. [Explanation of symbols]
[0069] 10 Laminate 11 Cathode active material layer 12 Negative electrode active material layer 13 Electrolyte layer 14 Positive electrode current collector 15 Negative electrode current collector
Claims
1. To obtain a laminate comprising: a positive electrode active material layer containing a positive electrode active material having a Li-deficient O2 type structure; a negative electrode active material layer containing a negative electrode active material containing Li; and an electrolyte layer provided between the positive electrode active material layer and the negative electrode active material layer; constraining the stack; and discharging the restrained laminate and then charging it a first time; A method for manufacturing a battery comprising the steps of:
2. Before the discharge, the negative electrode active material layer contains, as a negative electrode active material, a Si element and a Li—Si alloy. The method of claim 1 .
3. A method for manufacturing an all-solid-state battery, The method according to claim 1 or 2.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2002151074A
Lithium ion secondary battery and method of manufacturing the same
JP2010073571A
Non-aqueous electrolyte secondary battery
JP2011228273A
Battery system
JP2017112029A
Method for charging / discharging lithium secondary battery
JP2017152189A